Intracellular radar: Understanding γδ T cell immune surveillance and implications for clinical strategies in oncology - Cherry, Anne B. C.; Gherardin, Nicholas A.; Sikder, Hafiz I. (Frontiers in Oncology, 2022)
T cells play a key role in anticancer immunity, with responses mediated through a diversity of αβ or γδ T cell receptors. Although αβ and γδ T cells stem from common thymic precursors, the development and subsequent biological roles of these two subsets differ considerably. γδ T cells are an unconventional T cell subset, uniquely poised between the adaptive and innate immune systems, that possess the ability to recognize intracellular disturbances and non-peptide-based antigens to eliminate tumors. These distinctive features of γδ T cells have led to recent interest in developing γδ-inspired therapies for treating cancer patients. In this minireview, we explore the biology of γδ T cells, including how the γδ T cell immune surveillance system can detect intracellular disturbances, and propose a framework to understand the γδ T cell-inspired therapeutic strategies entering the clinic today.